Pengaruh Jiwa Kewirausahaan Pengurus dan Partisipasi Anggota Terhadap Perkembangan Usaha Koperasi Dengan Peran Pemerintah Sebagai Variabel Moderating - Riyanto, Cipto; Purbo Suseno, Gijanto (Universitas Koperasi Indonesia, 2024)
The existence of agricultural sector cooperatives is expected to be able to improve the welfare of its members and support West Java's economic growth, considering the large potential of the agricultural sector in this region. However, in reality, the cooperative business in the agricultural sector is currently experiencing a decline and its contribution to the economy of West Java is also relatively small. To develop a cooperative business, the entrepreneurial spirit of management and member participation is needed and supported by the government role. This research is intended to examine the effect of the management's entrepreneurial spirit and member participation on the cooperative business development which is moderated by government role. This type of research is quantitative with an associative approach. The data used is primary data obtained through questionnaires and secondary data obtained from the Online Data System (ODS) of the Ministry of Cooperatives and SMEs. Analysis of the collected data used the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The research results show that the entrepreneurial spirit of management and member participation affects the cooperative business development by 26.4%, while the rest is affected by other variables that were not studied. Partially, the entrepreneurial spirit of the management has a significantly affect on the cooperative business development, while member participation does not significantly affect the cooperative business development. Apart from that, from the moderation test it is known that government role does not significantly moderate the effect of the management's entrepreneurial spirit and member participation on the cooperative business development.